Bridging childhood to adulthood: the impact of early life stress on acute stress responses - Huang, Zheng; Bai, Huizhi; Yang, Ziyu; Zhang, Jingyu; Wang, Peishan; Wang, Xiaoyu; Zhang, Liang (Frontiers in Psychiatry, 2024)
Childhood trauma exerts enduring impacts on the physical and psychological well-being of individuals in adulthood, influencing their daily functioning. This study aims to investigate the impact of childhood trauma on stress recovery in adults, concentrating on heart rate variations during acute stress exposure. A cohort of 126 participants completed the Childhood Trauma Questionnaire (CTQ) and underwent the Trier Social Stress Test (TSST) to elicit acute stress, with continuous heart rate (HR) monitoring for stress recovery assessment. The results revealed a negative correlation between childhood trauma and stress recovery, prominently observed in instances of emotional neglect and abuse. Individuals with heightened childhood trauma exhibited protracted stress recovery following acute stress exposure. These findings contribute to the foundational framework for psychological interventions tailored to individuals with a history of childhood trauma.